Electrochemically Converting Liquid Cu2S‐Sb2S3 to Liquid Cu2Sb and Sulfur in Molten Salt at 730 °C. Issue 23 (2nd December 2021) - Guo, Yanyang; Li, Xianyang; Zhao, Zhuqing; Wang, Hongya; Qu, Jiakang; Hu, Zuojun; Xie, Hongwei; Yin, Huayi
Abstract: Conventional sulfide metallurgy suffers from SOx gas emission and high energy consumption, owing to the multiple‐step extraction processes and high temperatures that are above the melting point of the extracted metals. Herein, liquid Cu2 Sb alloy can be directly electrochemically extracted from the liquid Sb2 S3 ‐Cu2 S with no sulfide oxides emission in eutectic NaCl‐KCl molten electrolyte at 730 °C. The use of Sb2 S3 decreases the melting point of Cu2 S and the Sb decreases the melting temperature of Cu. The Sb2 S3 ‐Cu2 S mixture experiences three stages in the electrochemical desulfurization process: the insertion of Na + into liquid sulfides, the removal of S 2− and metallization, and finally the formation of uniform liquid Cu2 Sb alloy. The Sb2 S3 ‐Cu2 S can be completely electro‐converted into Cu2 Sb at 2.6 V for 6 hours. This study provides a straightforward and environmentally friendly route to electro‐synthesize liquid alloys from their molten sulfide minerals. Abstract : Paving the way : The conventional pyrometallurgical route extracts copper and antimony metals from their sulfide minerals through roasting, smelting, and refining processes. These steps call for high temperature and generate SO2 and CO2, which will cause intense energy consumptions and pollution. This paper paves a green electrochemical route to prepare liquid Cu2 Sb alloy from their molten sulfides at 730 °C without SOx (CO2 ) emissions.